Self-Assembly of Biopolymers: University of Bristol, UK 16-18th September 2013 - Earis F. Phillip (Faraday Discussions Vol. 166)
Soft matter has emerged as a coherent subject within the last ten years, and is of increasing relevance to interdisciplinary research at the interface of physical chemistry, physics, materials science and biology. Recently several exciting new directions have been pursued in this area, including developments in understanding amyloid fibrillization, liposome and polymersome self-assembly, DNA superstructure formation, biopolymer hydrogel self-assembly and how to control this to develop tissue scaffolds, and the control of biopolymer self-assemblies for applications in biomedicine. This volume focuses on the self-assembly of novel bio-hybrid materials, especially conjugates of proteins with polymers, glycosylation of proteins, polymer/virus hybrids etc